2006
DOI: 10.1167/iovs.05-0299
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-Induced Optic Nerve Degeneration and Nuclear Factor-κB p65

Abstract: TNF-alpha causes axonal degeneration with probable delayed loss of retinal ganglion cell bodies. NF-kappaB p65 may play a pivotal role in axonal degeneration, with the possible involvement of microglial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 39 publications
8
103
0
2
Order By: Relevance
“…Previous studies have shown that intravitreal TNF-␣ injections lead to morphological changes in mouse oligodendrocytes (Butt and Jenkins, 1994) and that the loss of oligodendrocytes in the optic nerve affects the susceptibility of axons to excitotoxicity (Coleman, 2005;Stys, 2005). In addition, TNF-␣ has been shown to cause axonal loss and subsequent death of RGCs in rats (Kitaoka et al, 2006). Axonal damage resulting from nerve injury has been shown in many studies to induce a delayed loss of RGC somata (Nakazawa et al, 2002a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that intravitreal TNF-␣ injections lead to morphological changes in mouse oligodendrocytes (Butt and Jenkins, 1994) and that the loss of oligodendrocytes in the optic nerve affects the susceptibility of axons to excitotoxicity (Coleman, 2005;Stys, 2005). In addition, TNF-␣ has been shown to cause axonal loss and subsequent death of RGCs in rats (Kitaoka et al, 2006). Axonal damage resulting from nerve injury has been shown in many studies to induce a delayed loss of RGC somata (Nakazawa et al, 2002a).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, exogenous TNF-␣ prevents RGC death after optic nerve damage (Diem et al, 2001), although other studies show that it can cause the loss of RGC axons and a delayed loss of somata (Kitaoka et al, 2006). As yet, there is no direct evidence that TNF-␣ contributes to RGC death in glaucoma, nor is there any mechanistic understanding of how this might occur.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, RGCs were significantly spared from degeneration in the STAT3-KO mice (Lupien et al, 2010). NFκB is a transcription factor expressed in neuronal and glial cells (Kitaoka et al, 2006) that regulates the expression of genes involved in inflammation, cell survival and apoptosis (Hayden & Ghosh, 2004). NFκB is multi-talented, able to upregulate anti-apoptotic factors but also activate pro-apoptotic pathways.…”
Section: Intracellular Pathwaysmentioning
confidence: 99%
“…We and other groups also demonstrated that intravitreal injection of TNF induces progressive optic nerve degeneration with slow RGC body death in mice 22 and rats. 23 These observations suggest that the TNF-induced neurodegeneration model may be useful in understanding the mechanism of axonal degeneration of the RGCs.…”
mentioning
confidence: 94%